Pengaruh Human Relationship, Disiplin Kerja, dan Kepuasan Kerja terhadap Kinerja Pegawai Dinas Koperasi & UKM Provinsi Jawa Tengah - Mukti, Fandy Cahyo; Astuti, Sih Darmi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to analyze the influence of human relation, work discipline, and job satisfaction on employee performance at the Cooperatives & SMEs Office of Central Java Province. This study uses a quantitative approach with a survey method that aims to determine the influence of Human Relation, Work Discipline, and Job Satisfaction on Employee Performance at the Cooperatives and SMEs Office of Central Java Province. The population in this study were all employees of the Cooperatives and SMEs Office of Central Java Province. The sample of this study was 91 respondents. The sampling technique used was non-probability sampling with a purposive sampling method. Data collection techniques were carried out online by distributing questionnaires using Google Forms with a Likert scale. The data obtained were then analyzed using the SPSS program.